Effect of Maximum Aggregate Size on the Bond Strength of Reinforcements in Concrete - Iqbal, S.; Ullah, N.; Ali, A. (Engineering, Technology & Applied Science Research, 2018)
The bond between reinforcements and concrete is the only mechanism that transfers the tensile stresses from concrete to reinforcements. Several factors including chemical adhesion, roughness and reinforcement interface and bar bearing affect the bond strength of reinforcements with concrete. This work was carried out considering another varying factor which is maximum aggregate size. Four mixes of concrete with similar compressive strengths but different maximum aggregate sizes of 25.4mm, 19.05mm, 12.7mm and 9.53mm were used with the same bar size of 16mm. Compressive strength, splitting tensile strength and bond strength for each concrete mix were studied. Test results depict a slight increase in compressive and splitting tensile strength with decrease in maximum aggregate size. The bond strength remained at the same level with decrease in maximum aggregate size except at maximum aggregate size of 9.53mm when there was a drop in bond strength, despite better compressive and splitting tensile strengths. ACI-318 and FIB-2010 codes equation for bond strength calculation work well only when the maximum aggregate size is 12.7mm and above. Therefore, maximum aggregate size is critical for bond strength when smaller size aggregates are used.